Daftar Pustaka, Catatan Kaki, dan Kutipan - Galang Juliansyah; Muhammad Irham Prasetyo; Redoh Muhammad Abi; M. Habibbullah; Reza Azirpa; Ira Yuniati; Ade Tiara Yulinda (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Bibliography, footnotes, and quotations are important elements in academic writing. All three serve as a form of acknowledgment of the information sources used, enhance the credibility of the writing, and help prevent plagiarism. A bibliography contains all references used as a basis for preparing an academic paper, footnotes provide additional information or citation sources at the bottom of the page, while quotations are used to strengthen the discussion by citing opinions or research findings from other sources. Writing that follows academic conventions will make it easier for readers to trace reference sources and strengthen the validity of the information presented. Therefore, an understanding of how to write bibliographies, footnotes, and quotations is highly necessary for students, researchers, and writers in producing quality and ethical academic work.